2005
DOI: 10.1111/j.1439-0523.2005.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of quantitative trait loci related to lodging resistance and associated traits in bread wheat

Abstract: Lodging is a major constraint to increasing yield in many crops, but is of particular importance in the small-grained cereals. This study investigated the genetic contro! of lodging and component traits in wheat through the detection of utiderlying quantitative trait loci (QTL), The analysis was based on the identittcation of genomic regions which affect various traits related to lodging resistance in a population of 96 doubled haploid lines of the cross 'Milan' x 'Catbird", mapped using 126 microsatellite mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 24 publications
4
60
1
1
Order By: Relevance
“…Marker-assisted selection has potential to improve the efficiency of selection for lodging resistance in breeding programs. Thus, QTL studies on the correlation between LD and other traits have been performed in several cereal crops, such as soybean, rice (Kashiwagi et al, 2008;Zhu et al, 2008), wheat Zuber et al, 1999;Börner et al, 2002;Kelbert et al, 2004;Verma et al, 2005), maize (Flint-Garcia et al, 2003), and field pea. However, little information related to barley LD has been reported to date (Sameri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Marker-assisted selection has potential to improve the efficiency of selection for lodging resistance in breeding programs. Thus, QTL studies on the correlation between LD and other traits have been performed in several cereal crops, such as soybean, rice (Kashiwagi et al, 2008;Zhu et al, 2008), wheat Zuber et al, 1999;Börner et al, 2002;Kelbert et al, 2004;Verma et al, 2005), maize (Flint-Garcia et al, 2003), and field pea. However, little information related to barley LD has been reported to date (Sameri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these genes have been *Corresponding authors (email: penghuiru@cau.edu.cn; qxsun@cau.edu.cn) exploited to breed many semidwarf cultivars with high yield potential. Recently, along with the advent of molecular quantitative genetics, about 50 quantitative trait loci (QTLs) for wheat plant height have been identified using the constructed molecular genetic linkage maps [3][4][5][6][7][8][9][10][11][12][13][14][15]. However, QTL mapping of plant height in wheat was only focused on the performance of this trait at the maturing stage.…”
mentioning
confidence: 99%
“…Lodging resistance in cereals is determined by both genetic and environmental factors (Verma et al, 2005). Many authors have observed that lodging resistance of barley is affected by the physical and morphological properties of the stem (Chen et al, 2014).…”
Section: Resultsmentioning
confidence: 99%